2016 IEEE International Conference on Consumer Electronics (ICCE) 2016
DOI: 10.1109/icce.2016.7430623
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of taperéd cap floating sleeve antenna for interstitial microwave ablation for liver tumor

Abstract: Microwave ablation (MWA) is relatively safe and efficient treatment method for the patients suffering with liver tumors. The antenna is integral part of the MWA setup. The optimized design of antenna play important role in investigating the effectiveness of MWA therapy. Tapered Cap Floating Sleeve Antenna was simulated, designed and optimized to treat the malignant liver tumors. The strength of tapered cap floating sleeve facilitates the antenna to be inserted into the liver tissue without requiring any insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The most common antenna structure used for interstitial MWA is the coaxial antenna. Till now many researchers have presented several coaxial antennas such as monopole antenna, dipole antenna, choked antenna, slot antenna, and floating sleeve antenna [5]- [48], [9], [49]. Each one of the stated antenna designs has its characterizing performance regarding the heating pattern, backward heating, and the transient behavior under heating [5].…”
Section: Antenna Structures Used For Cancer Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common antenna structure used for interstitial MWA is the coaxial antenna. Till now many researchers have presented several coaxial antennas such as monopole antenna, dipole antenna, choked antenna, slot antenna, and floating sleeve antenna [5]- [48], [9], [49]. Each one of the stated antenna designs has its characterizing performance regarding the heating pattern, backward heating, and the transient behavior under heating [5].…”
Section: Antenna Structures Used For Cancer Ablationmentioning
confidence: 99%
“…It has been used by the physicians, since the beginning of the twentieth century, in the treatment of various forms of tumors. It was found that tumor cells are more affected by the heat than normal cells [5]. Nowadays, thermal tumor ablation became an important candidate in the treatment of many types of cancerous tumors such as the liver, lung, kidney and breast [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…The tail of the comet inevitably damages the normal tissues along the shaft of MW antenna. Therefore, modified designs have been proposed to improve radiation properties of antennas by adding a choke or sleeve outside the antennas [30][31][32][33][34], which can effectively suppress the reverse heating. Unfortunately, this is at the expense of an increase in the diameter of the antenna.…”
Section: Introductionmentioning
confidence: 99%
“…The simple devices to perform an interstitial microwave hyperthermia comprised of a microwave generator, a microwave applicator/antenna, and a flexible coaxial cable to connect the antenna to the microwave generator [4]. Using these thin microwave hyperthermia devices has many advantages: avoiding the possible damage of surrounding tissues and reducing the procedural risks [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies designed microwave sleeve antennas for hepatic microwave hyperthermia using simple models of both tumors and livers-which did not reflect the actual effect of the anatomical structures and blood circulation on the temperature distribution [5][6][7][8][9][10]. This work aims to design a microwave sleeve antenna capable of heating hepatic tumors using realistic 3D liver and tumor models.…”
Section: Introductionmentioning
confidence: 99%